Description of Worship Routine and Burnout Incidence in Medical Students of Universitas Islam Negeri Syarif Hidayatullah Jakarta - Alfani Naqiya Shidqiyah; Fika Ekayanti; Prasetiyawan Prasetiyawan; Marita Fadhilah; Adhi Wibowo Nurhidayat (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2023)
Background: The latest study in 2021 regarding the incidence of burnout in medical students at 29 medical faculties shows that 1,729 students experience high category burnout. Indonesia as a country with the world's largest Muslim population, Islamic worship is their way of life. Islam teaches its followers that worship routine will help them to live in peace. Religious practices both individually and socially have been shown to help reduce symptoms of mental disorders and improve mental health include burnout. The aims of this study is to find out the incidence of burnout and worship routine among students in the preclinical year of the State Islamic University (UIN) Syarif Hidayatullah Jakarta.Subjects and Methods: It was a descriptive study design with total sampling on medical students batch 2018 to 2020. Data were collected by questionnaires and analysed descriptively using SPSS 28.0. Results: From 282 respondents (90.1% response rate), results showed that most students had high worship routine (60.6%), and only 3.5% had low worship routine. The incidence of burnout were about 11%, with 44% of them had high risk for burnout. Among the burnout students, most of them had low worship routine 50%, 24.8% moderate routine, and 0.6% high routine.Conclusion: Most of the preclinical year medical students who experience burnout have low worship routines